Dnamatch2: An open source software to carry out large scale database searches of mixtures using qualitative and quantitative models. (December 2017) - Bleka, Ø.; Bouzga, M.; Fonneløp, A.; Gill, P.
Abstract: A very fast, efficient, fully automated database search algorithm has been implemented as an open source R-package dnamatch2 . It carries out both "crime-stain-against-crime-stain" and "reference-against-crime-stain" comparisons, where the stains can be partial mixture profiles with allele drop-out. In this article we demonstrate how the algorithm works using a large set of crime-stain and reference profiles as an example.